2022
DOI: 10.12659/ajcr.937195
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Hamartoma: A Case Report and Literature Review

Abstract: Patient: Male, 19-year-old Final Diagnosis: Splenic hamartoma Symptoms: Abdominal pain Medication:— Clinical Procedure: Laparoscopic splenectomy Specialty: Surgery Objective: Rare disease Background: Splenic hamartoma (SH) is a benign vascular lesion, usually found incidentally on abdominal images or at autopsy. Only around 200 cases have been reported since 1861, when SH was first described by Roki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…However vascular tumors are frequent lesions of the spleen, splenic hamartoma is rare. Only around 200 cases have been reported [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However vascular tumors are frequent lesions of the spleen, splenic hamartoma is rare. Only around 200 cases have been reported [2].…”
Section: Discussionmentioning
confidence: 99%
“…Splenic hamartoma is a rare benign vascular proliferative neoplasm of the vascular endothelial lining cells [1]. They are often present as a solitary mass, but multiple lesions have been reported [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a study including 32 patients with splenic hemangiomas,11 of the patients had splenic lesions characterized as such based on their typical imaging findings on CT and US alone, while all were managed successfully with observation [33]. Splenic hamartomas are very rare splenic lesions, with only around 200 cases reported since 1861 [34]. A review of the autopsy series has shown that the incidence of splenic hamartoma ranges from 0.024% to 0.13%.…”
Section: Lesion-specific Imaging Characteristicsmentioning
confidence: 99%
“…Females usually have larger hamartomas, which may reflect a hormonal influence. Some splenic hamartomas have rapid growth, and larger lesions may rupture [34]. On US, they appear as solid hypoechoic masses; when hemorrhage or cystic changes are present, they can be Splenic hamartomas are very rare splenic lesions, with only around 200 cases reported since 1861 [34].…”
Section: Lesion-specific Imaging Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation